Analisis Hadits Tentang Keharusan Pemimpin Dari Bani Quraisy - Jaya, Canra Krisna; Lubis, Rahmat Kurnia (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2021)
This article aims to explain how to understand the hadith about the leadership of the Banu Quraysh. This study uses descriptive analysis method, with a qualitative approach. This article concludes, First, textually there is no debate about the hadith of the Bani Quraysh leadership and Islamic thinkers accept this. Second, the Banu Quraysh became a sunatullah rule, becoming a leader in global coverage, but not regionally. Third, leadership in the regional scope provides opportunities for leaders who come from non-Bani Quraysh to occupy leadership positions. Fourth, the opportunity to become a leader for the non-Ban Quraysh must still pay attention to the criteria or conditions for becoming a leader. Starting from who chooses then who will be chosen.